The adoption of ISO standards in Brazil, Iberian Peninsula and United Kingdom in information and documentation A comparative study - Nascimento, Natalia Marinho do [UNESP]; Moro Cabero, Maria Manuela; Pomim Valentim, Marta Ligia [UNESP] (Emerald Group Publishing Ltd, 2018)
Purpose The use of standards is currently characterized by International Organization for Standardization (ISO) as essential for the efficient development of products, processes, services and systems in organizations; that is the norm-profit-measuring methodology Toolkit. From an impact-analysis perspective, the purpose of this paper is to compare the existing published standards in the area of archival science and documentation in Brazil, by the hand of the Brazilian Association of Technical Standards (ABNT); Portugal (NP), by the Portuguese Institution of Quality (IPQ); and in Spain (UNE), by the Spanish Association for Standardization and Certification (AENOR). Finally, this paper aims to observe the convergences and divergences among these countries with respect to the first country standards organization, United Kingdom (UK), by the British Standards Institution (BSI). This paper is an extract of a deeper investigation about behaviors, uses and impact of ISO's standards. Design/methodology/approach The methodology consists in a qualitative and quantitative comparative study, carried out through the analysis of the technical contents of the standards present in the catalogs available on the ABNT, IPQ, AENOR and BSI websites. It compares the main existing divergences in adoption, collaboration, elaboration, volume, working-group dynamism, editing schedules, costs and groups of standards. Findings The analysis allowed to observe the relevance of the technical standards in the studied countries and the advantages of the adoption of ISO for the dissemination of contents. For instance, the use and application of these standards for the development of archival and records management activities is considered to benefit the professionals to decrease the time of implementation and execution of the archival activities and allow continuous assessment. Besides ensuring quality in the archival processes, standardization evidences the complexity within organizational environments inherent to the metamorphosis of each's functional context. Originality/value This paper contributes with an original analysis of how the technical standards of the Archival and Records Management area are published and used in Brazil, Iberian Peninsula and the UK.
Keywords: Records management; Documentation; Standardization; Archival information